TOWARDS A HOLISTIC AND INCLUSIVE PEDAGOGY FOR STUDENTS FROM DIVERSE LINGUISTIC BACKGROUNDS - Bisai, Samrat; Singh, Smriti (TEFLIN Journal, 2020)
In a multilingual classroom, students come from various cultural, linguistic, and racial backgrounds. They have different ideologies, opinions, and needs. In this regard, ‘one size fits all’ pedagogy is not only irrelevant but also absurd because the instructions and interactions in the classroom do not cater to the needs of all the students. Therefore, a carefully planned pedagogy that addresses the needs of the individual learners differently in the classroom is needed. In this scenario, implementing multilingual pedagogy in the classroom might be a better idea as it can address the needs of individual learners by making education inclusive and accessible to all. Multilingual pedagogy here is defined as a set of principles that are used to varying degrees in different approaches depending on the teaching context, learners, and curriculum (Neuner, 2004). This paper discusses various approaches, methods, and strategies within the framework of multilingual pedagogy that can be implemented in a classroom consisting of students from diverse linguistic backgrounds. To provide a clear picture of the theoretical ideas, the practical implementation of the ideas in some schools are also discussed. During the implementation, it is indicated that multilingual pedagogy holds the potential to enhance student learning.